Petrophysical characterisation of reservoir intervals in well-X and well-Y, M-Field, offshore Douala Sub-Basin, Cameroon - Gilbert M. Chongwain; Olawale Olakunle Osinowo; Marie J. Ntamak-Nida; S. E. A. Biouele; Eric. N. Nkoa (Journal of Petroleum Exploration and Production Technology, 2018)
Abstract Studies for the characterization of hydrocarbon reservoirs using well logs have been carried out in the M-Field of the Douala Basin to evaluate the hydrocarbon prospectivity, delineate hydrocarbon zones and determine the petrophysical properties of the identified reservoir rocks. Data from two wells comprising gamma ray, resistivity, neutron, density logs were used. Gamma ray log was used for lithologic discrimination; resistivity log was employed to identify formation fluid based on electrical responses of reservoir formations, while combined density and neutron logs were used to estimate reservoir porosity, as well as ascertain hydrocarbon type where present. Four hydrocarbon bearing reservoirs were delineated in the study area; one in Well-X (X 2) with a thickness of 6.2 m and three others in Well-Y (Y 1, Y 2, Y 3) with thicknesses of 19.2 m, 7.6 m and 78.7 m, respectively. Neutron–density crossplots indicate heterogeneous reservoir matrix comprising of sand, limestone and dolomite. The reservoirs were correlated using gamma ray log and were found to be discontinuous across the wells. The petrophysical parameters of the reservoirs evaluated indicate porosity, water-saturation and hydrocarbon-saturation values of X 2 to be 20.8%, 30.8% and 69.2%, respectively, and the average porosity, water saturation and hydrocarbon saturation of the Well-Y reservoirs to be 40.2%, 18.3% and 81.7%, respectively. The porosity value indicates medium–high formation porosities and oil as the dominant hydrocarbon type. The crossplot of water-saturation and porosity revealed that the grain size variation of the reservoirs ranges from fine-grained to silty sands. The bulk volume water (BVW) values for the M-Field reservoirs suggest that they are homogeneous and at irreducible water saturation (Swirr) and hence will produce water-free hydrocarbons.